Hydrodynamical simulations of the stream-core interaction in the slow merger of massive stars - Ivanova, N; Podsiadlowski, P; Spruit, H (Oxford University Press, 2002)
We present detailed simulations of the interaction of a stream emanating from a mass-losing secondary with the core of a massive supergiant in the slow merger of two stars inside a common envelope. The dynamics of the stream can be divided into a ballistic phase, starting at the L1 point, and a hydrodynamical phase, where the stream interacts strongly with the core. Considering the merger of a 1- and 5-M⊙ star with a 20-M⊙ evolved supergiant, we present two-dimensional hydrodynamical simulations using the prometheus code to demonstrate how the penetration depth and post-impact conditions depend on the initial properties of the stream material (e.g. entropy, angular momentum, stream width) and the properties of the core (e.g. density structure and rotation rate). Using these results, we present a fitting formula for the entropy generated in the stream–core interaction and a recipe for the determination of the penetration depth based on a modified Bernoulli integral.